New options for targeting TRPV1 receptors for cancer treatment: odorous Chinese herbal medicine - Zhang, Minghui; Wang, Zongao; Liu, Shaojun; Li, Yuxuan; Gong, Yanting; Liu, Min (Frontiers in Oncology, 2025)
Vanilloid1 (TRPV1), a subfamily of transient receptor channels, is one of the non-selective calcium channels, which is a bridge between cellular response and extracellular environmental networks, and is involved in a variety of pathophysiological processes. It is also involved in the process of cancer occurrence and progression, and researchers are revealing its role in cancer. In this paper, we review the expression and significance of TRPV1 receptor in various cancer cell types, the role of TRPV1 in the apoptosis-proliferation balance, cancer cell invasion and metastasis, and tumor micro-environment, with emphasis on the mechanisms by which TRPV1 receptor mediates inflammatory response, immune system, and thus regulates cancer. We discussed the latest directions and current challenges of TRPV1 receptor-targeting therapy for cancer, and summarized the odorous traditional herbs that modulate TRPV1 receptors, with a view to developing anti-tumor drugs targeting TRPV1 receptors in the future.